Mechanistic insights of CRISPR/Cas‐mediated genome editing towards enhancing abiotic stress tolerance in plants - Bhat, Mujtaba Aamir; Mir, Rakeeb Ahmad; Kumar, Vijay; Shah, Ali Asghar; Zargar, Sajad Majeed; Rahman, Safikur; Jan, Arif Tasleem (Physiologia plantarum, 2021)
Abiotic stresses such as temperature (high/low), drought, salinity, and others make the environment hostile to plants. Abiotic stressors adversely affect plant growth and development; and thereby makes a direct impact on overall plant productivity. Plants confront stress by developing an internal defense system orchestrated by compatible solutes, reactive oxygen species scavengers and phytohormones. However, routine exposure to unpredictable environmental stressors makes it essential to equip plants with a system that contributes to sustainable agricultural productivity, besides imparting multi‐stress tolerance. The sustainable approach against abiotic stress is accomplished through breeding of tolerant cultivars. Though eco‐friendly, tedious screening and crossing protocol limits its usage to overcome stress and in attaining the goal of global food security. Advancement on the technological front has enabled adoption of genomic engineering approaches to perform site‐specific modification in the plant genome for improving adaptability, increasing the yield and in attributing resilience against different stressors. Of the different genome editing approaches, CRISPR/Cas has revolutionized biological research with wider applicability to crop plants. CRISPR/Cas emerged as a versatile tool in editing genomes for desired traits in highly accurate and precise manner. The present study summarizes advancement of the CRISPR/Cas genome editing tool in its adoption to manipulate plant genomes for novel traits towards developing high‐yielding and climate‐resilient crop varieties.